Changing trends in pacemaker and implantable cardioverter defibrillator generator advisories. - Maisel WH; Stevenson WG; Epstein LM (Pacing & Clinical Electrophysiology, 2002)
Pacemaker and implantable cardioverter defibrillator (ICD) generator recalls and safety alerts (advisories) occur frequently, affect many patients, and are increasing in number and rate. It is unknown if advances in device technology have been accompanied by changing patterns of device advisory type. Weekly FDA Enforcement Reports from January 1991 to December 2000 were analyzed to identify all advisories involving pacemaker and ICD generators. This article represents additional analysis of previously cited advisories and does not contain additional recalls or safety alerts over those that have been previously reported. The 29 advisories (affecting 159,061 devices) from the early 1990s (1991-1995) were compared to the 23 advisories (affecting 364,084 devices) from the late 1990s (1996-2000). While the annual number of device advisories did not change significantly, ICD advisories became more frequent and a three-fold increase in the number of devices affected per advisory was observed. The number of devices affected by hardware advisories increased three-fold, due primarily to a 700-fold increase in electrical/circuitry abnormalities and a 20-fold increase in potential battery/capacitor malfunctions. Other types of hardware abnormalities (defects in the device header, hermetic seal, etc.) became less common. The number of devices recalled due to firmware (computer programming) abnormalities more than doubled. The remarkable technological advances in pacemaker and ICD therapy have been accompanied by changing patterns of device advisory type. Accurate, timely physician and patient notification systems, and routine pacemaker and ICD patient follow-up continue to be of paramount importance.